Impact of chronic hepatitis C on mortality in cirrhotic patients admitted to intensive-care unit. Issue 1 (December 2016) - Álvaro-Meca, Alejandro; Jiménez-Sousa, María; Boyer, Alexandre; Medrano, José; Reulen, Holger; Kneib, Thomas; Resino, Salvador
Abstract Background Cirrhosis and severe sepsis are factors associated with increased mortality in intensive care unit (ICU), but chronic hepatitis C (CHC) has been less studied in ICU. The aim of this study was to analyze the impact of CHC on the mortality of cirrhotic patients admitted to ICU according to severe sepsis and decompensated cirrhosis. Methods We carried out a retrospective study based on CHC-cirrhotic patients (CHC-group) admitted to ICU (n  = 1138) and recorded in the Spanish Minimum Basic Data Set (2005–2010). A control-group (randomly selected cirrhotic patients without HIV, HBV, or HCV infections) was also included (n  = 4127). The primary outcome variable was ICU mortality. The cumulative mortality rate on days 7, 30, and 90 in patients admitted to the ICUs was calculated by dividing the number of deaths by the number of patients admitted to the ICU. The adjusted hazard ratio (aHR) for death in the ICU was estimated through a semi-parametric Bayesian model of competing risk. Results The CHC-group had a higher cumulative incidence of severe sepsis than the control-group in compensated cirrhosis (37.4 vs. 31.1 %;p  = 0.024), but no differences between the CHC-group and the control-group in decompensated cirrhosis were found. Moreover, a higher cumulative incidence of severe sepsis was associated with decompensated cirrhosis compared to compensated cirrhosis in the control-group (40.1 vs. 31.1 %;p  < 0.001) whereas this was not observed in the CHC group (38.1 vs. 37.4 %;p  = 0.872). The CHC-group had higher cumulative mortality than the control-group by days 7 (47 vs. 41.3 %;p  < 0.001), 30 (78.5 vs. 73.5 %;p  < 0.001), and 90 (96.3 vs. 95.9 %;p  < 0.001). In a competitive risk model, the CHC-group had a higher risk of dying if the ICU course was complicated by severe sepsis (adjusted hazard ratio (aHR) = 1.19;p  = 0.003), but no significant values in patients with absence of severe sepsis were found (aHR = 1.09;p  = 0.068). When patients were stratified by cirrhosis stage and severe sepsis, CHC patients with compensated cirrhosis had the higher risk of death if they had severe sepsis (aHR = 1.35;p  = 0.002). Moreover, the survival was low in patients with decompensated cirrhosis and severe sepsis but we did not find significant differences between CHC-group and control-group. Conclusions CHC was associated with an increased risk of death in cirrhotic patients admitted to ICUs, particularly in patients with compensated cirrhosis and severe sepsis.